Experimental investigation on the properties and microstructure of magnesium oxychloride cement prepared with caustic magnesite and dolomite - Liu, Zhuangzhuang; Wang, Shuai; Huang, Jian; Wei, Zhenhua; Guan, Bowen; Fang, Jianhong (Construction & building materials, 2015)
[Display omitted] •We made magnesium oxychloride cements with caustic magnesite and dolomite.•The minimum of active MgO in magnesium oxychloride is suggested by 33.4wt.%.•We defined two very important parameters in MgO–MgCl2–H2O system, K1 and K2.•The water resistance coefficient of magnesium oxychloride is not related with the compressive strength. Magnesium oxychloride cements (MOCs) with different amount of active magnesium oxide were prepared with caustic magnesite and dolomite. The fluidity, compressive and flexural strength were measured. After that, the MOCs were analyzed by XRD and SEM. The results indicated that MOCs prepared with caustic magnesite and dolomite obtained a good engineering performance. The result suggested that the minimum active MgO content used in MOCs should be 33.4wt.%. At the same time, this study shows that the water resistance coefficient of MOC is concerned with the balance of hydration and hydrolysis reactions which provides two main modification approaches, improving the hydration rate or preventing the reverse reaction. Meanwhile, it is shown in the experiment that there is no significant relationship between the water resistance coefficient and the compressive strength of MOCs.